Differentiated Learning in Physics Lessons to Increase Creativity and Knowledge of Class X Students - Indra Dami Susanti; Ishafit; Moh. Irma Sukarelawan (South Sulawesi Education Development (SSED), 2024)
Student learning outcomes are still low because the physics learning taught is not yet on target even though there are many factors that influence this because the teaching system is still focused in one direction. The aim of this research is to carry out differentiated learning according to students' learning styles so that students can be more creative in finding out the material provided by the teacher without any sense of compulsion, so that the learning that students undergo can be meaningful. This type of research is quantitative research with an experimental approach method. In this design, the researcher gives an initial test to both classes to determine the experimental and control classes before receiving treatment. The research sample was students of SMA Negeri 4 PPU class X.1 as the experimental class and class X.2 as the control class which was determined using non-random sampling techniques. The research data is in the form of a pretest, a diagnostic test to determine students' learning styles, creativity during learning and a posttest to determine students' physics knowledge. Validity data for creativity instruments and questions used Winstep software and for creativity used normality, homogeneity, Wicoxon and Mann Whitney tests, calculations were carried out using SPSS version 26 and Excel. The results obtained using the non-parametric test that the researcher carried out were (1) there was an effect of differentiated learning on students' creativity and knowledge of physics with a sig value. 0,000. (2) there are differences in student creativity and physics knowledge learning outcomes between the experimental class and the control class where the sig value is 0.000 <0.05. (3) Based on the results of research conducted by researchers using non-parametric tests, it can be concluded that classes that receive treatment are more effective in increasing their creativity and knowledge.